Air quality assessment in indoor and outdoor environments: A review. (2022) - Prabhakaran, J.; Jayabal, S.; Ramesh Kumar, A.; Vinoth, V.
Abstract: Air quality impacts both the environment and health conditions of people in living space. The air quality assessment in indoor and outdoor environments is essential to resolve the health impacts caused by environmental degradation. The present investigation is focused on the study of air quality assessment in three major areas including Vehicle Cabins, inside buildings and outdoor environments. The studies of air quality by scientists and researchers for the past 33 years have been reviewed and reported. As the air spreadable disease can blowout when people with positive infections cough, sneeze, spewing nasal and throat secretions into the air including COVID-19 transmitted through contact with respiratory droplets through the air, this comprehensive report on air quality characteristics will provide awareness for human safety and promote more research for the invention of comfort air quality in human living space.